PELAKSANAAN PENILAIAN AUTENTIK DALAM PEMBELAJARAN BAHASA JEPANG DI KELAS X SMK NEGERI 1 SINGARAJA BERBASIS KURIKULUM 2013 - Apriliani, Kadek; Hermawan, Gede Satya; Yeni, Yeni (Jurnal Pendidikan Bahasa Jepang Undiksha, 2021)
The purpose of this paper is to describe the implementation of authentic assessment and assessment instruments used in carrying out authentic assessments in Japanese language learning in class X SMK Negeri 1 Singaraja. Data collection methods used in this study were observation, interviews and document study. Data were analyzed using qualitative descriptive analysis. The subjects used in this study were class X SMK Negeri 1 Singaraja. The object of this research is the implementation and assessment instruments used for the implementation of authentic assessment in Japanese language learning in class X SMK Negeri 1 Singaraja. The results showed that the implementation of authentic assessment in Japanese language learning in class X SMK Negeri 1 Singaraja includes knowledge assessment using oral test techniques and assignments. Attitude assessment uses observation or observation techniques and attitude assessment journals. Assessment of skills using performance appraisal techniques. The assessment instruments used for the implementation of authentic assessment in Japanese language learning in class X SMK Negeri 1 Singaraja are online RPP, syllabus, knowledge assessment rubric, attitude assessment journal, speaking skills assessment rubric, writing skills assessment rubric and listening skills assessment rubric.